Efeito da lectina Concanavalina A (CON A) sobre a ativação in vitro de folículos primordiais caprinos - Portela, Antonia Moemia Lúcia Rodrigues (2013)
The aim of this study were to evaluate the effect of different concentrations of Concanavalin A (Con A) and FSH on activation, and survival in vitro growth of goat primordial follicles, as well as investigating the effects of Con A and FSH on the expression of mRNA for PCNA, KL, c-Kit, BMP-15 and GDF-9. For this, ovarian cortex fragments were in vitro cultured for 1 to 6 days in α-MEM+ supplemented with 0, 5, 10, 20 or 40 μg/mL of Con A lectin (experiment 1). At the end of the growing period, the fragments of ovarian cortex were fixed for histology. Next, we evaluated the percentage of primordial follicles or under development. After determination of the concentration of Con A more efficient (10 μg/mL), fragments of ovarian cortex were cultured in situ for 6 days in α-MEM+ alone or supplemented with 50 ng/mL of FSH, 10 μg/mL of Con A or both (experiment 2). Tissues from the control uncultured or after culture in different treatments were fixed for histology or stored at -80ºC to assess the expression profile of mRNA for PCNA, KL, c-Kit, BMP-15 and GDF-9. The results of Experiment 1 demonstrated that after 6 days of culture, the percentage of developing follicles was significantly higher in samples cultured with α-MEM+ supplemented with 10 and 40 μg/mL Con A, when compared to the other treatments (P <0.05). In experiment 2, the presence of FSH, or both Con A promoted a reduction in the percentage of primordial follicles and increase developing follicles compared to control medium (α-MEM+). After 6 days of culture, the presence of FSH promoted an increase in mRNA levels for PCNA, but this effect was blocked by Con A. Moreover, the Con A increased mRNA levels for c-KIT compared to the control not grown, but Con A or Con A and FSH both reduced the levels of mRNA for KL. Furthermore, a reduction of BMP-15 mRNA was observed in follicles cultured in control medium, but the presence of FSH inhibited this reduction. Furthermore, Con A promoted an increase in levels of GDF-9 mRNA after in vitro culture. In conclusion, the Con A alone or in combination with FSH promote activation of primordial follicles goat after 6 days of in vitro culture and regulate the expression of mRNA for PCNA, KL, c-Kit, BMP-15 and GDF-9